(3JQLjM GdSOd Ydi GdbHUs - (3SjO CMeO Hf ESeg,J (B1392 (3g` s ((3ehjJGfjG s)
(3ChdgG (B:s
(3QLM GdSOd Ydi GdbHU ai bWQfG gPG hEf cfG eYkG ef GdSfI HeG SCPcQg Ef TGA Gddg JYGdi ai SJI aUhd hNGJeI s
(3BNQgG (B:s
(3adGjUOfc CgjG GdCN GdeMbb eG YSi Cf Jba Ydjg ai gPg GdhQbGJ ef GdNWC s
(3eNWhWI MOjKI ecJhHI HGdMHQ GdCRQb hYdi hQb VYja eeG LYdg QOFjkGs
(3hYdjgG RjGOGJ hTQhM Hbde QUGUs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeYgO GdehQjJGfi ddHMK GdYdei (B((3abg eGdc (B42) s
Keywords: (3Gdabg GdeGdcjs